2017
DOI: 10.1149/2.1411707jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Evaluation of Corrosion Inhibiting Layers Formed in a Defect from Lithium-Leaching Organic Coatings

Abstract: 14This work presents the electrochemical evaluation of protective layers generated in a 15 coating defect from lithium-leaching organic coatings on AA2024-T3 aluminum 16 alloys as a function of neutral salt spray exposure time. Electrochemical impedance 17 spectroscopy was used to study the electrochemical properties on a macroscopic 18scale. An electrochemical model allowed to quantitatively link the electrochemical 19 behavior with the physical model of the layer in the damaged area as studied by 20 scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 35 publications
(75 reference statements)
2
41
0
2
Order By: Relevance
“…Compared with the unexposed sample and the sample without Li‐carbonate, the phase angle plot of the sample with the Li‐carbonate loaded coating showed a broadening of the time‐constant related with formation of the oxide layer and increases phase angle values at the lower frequency range which indicates improved corrosion resistance. This behaviour is characteristic for the Li‐leaching coating technology on AA2024‐T3 . A similar behaviour was observed for the samples with the Li‐carbonate loaded coatings on the AA7075W (Figure B) and the AA5083W (Figure C) after 168‐hour NSS exposure.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Compared with the unexposed sample and the sample without Li‐carbonate, the phase angle plot of the sample with the Li‐carbonate loaded coating showed a broadening of the time‐constant related with formation of the oxide layer and increases phase angle values at the lower frequency range which indicates improved corrosion resistance. This behaviour is characteristic for the Li‐leaching coating technology on AA2024‐T3 . A similar behaviour was observed for the samples with the Li‐carbonate loaded coatings on the AA7075W (Figure B) and the AA5083W (Figure C) after 168‐hour NSS exposure.…”
Section: Resultssupporting
confidence: 78%
“…Each graph shows a measurement of an unexposed sample to demonstrate the initial stage of the defect area with the native aluminium oxide and the measurements of the samples with and without Li‐carbonate after 168‐hour NSS exposure. Figure A shows the typical response of the impedance modulus (top) and phase angle (bottom) of a AA2024‐T3 coated with and without Li‐carbonate as leaching inhibitor . The impedance modulus (Figure A top ) of the sample with the Li‐carbonate loaded coating increased in the middle (10 1 ‐10 3 Hz) and low frequency (10 −1 ‐10 −2 Hz) ranges compared with the samples without Li‐carbonate and the unexposed sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with the observations when lithium-salts are used as leachable corrosion inhibitor in organic coatings. 15 …”
Section: Mechanism Of Formation-the Results Of This Investigationmentioning
confidence: 99%
“…15 Recently, new examples of the corrosion protective properties of lithium on aluminum were published. Gharbi et al observed a protective Li/Al surface film on Al-Cu-Li 2050-T3 alloy after polarization.…”
mentioning
confidence: 99%